2004
DOI: 10.1080/j.1440-1614.2004.01365.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Risk Factors for Adolescent Antisocial Behaviour: An Australian Longitudinal Study

Abstract: Few studies have assessed early predictors of antisocial behaviour in Australia and the current results can be used to inform prevention programs that target risk factors likely to lead to problem outcomes for Australian youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
1
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 50 publications
3
61
1
7
Order By: Relevance
“…This picture contrasts with the one that is found in German [12], where the societal problem imposed by criminal minors is notable less severe. In an epidemiological study, developed in collaboration with Dr. Daniel Martins de Barros and Dr. Antônio Serafim de Pádua (NUFOR-Ipq-FMUSP), which aimed to define the psychiatric profile of near one thousand incarcerated minors, we reached the conclusion that the most prevalent psychiatric condition in this cohort is antisocial personality disorder associated with the use of drugs (ICD-10: F10-19); at the same time, we found that certain psychiatric disorders tend to be less prevalent in this population and less related to re-incarceration than reported by previous international studies, focused on the psychiatric profile of young offenders from developed countries; i.e., [13]. Our study is under the final stage of peer-review in a well-known Journal.…”
contrasting
confidence: 45%
“…This picture contrasts with the one that is found in German [12], where the societal problem imposed by criminal minors is notable less severe. In an epidemiological study, developed in collaboration with Dr. Daniel Martins de Barros and Dr. Antônio Serafim de Pádua (NUFOR-Ipq-FMUSP), which aimed to define the psychiatric profile of near one thousand incarcerated minors, we reached the conclusion that the most prevalent psychiatric condition in this cohort is antisocial personality disorder associated with the use of drugs (ICD-10: F10-19); at the same time, we found that certain psychiatric disorders tend to be less prevalent in this population and less related to re-incarceration than reported by previous international studies, focused on the psychiatric profile of young offenders from developed countries; i.e., [13]. Our study is under the final stage of peer-review in a well-known Journal.…”
contrasting
confidence: 45%
“…Early risk factors such as harsh parenting, maternal anxiety, parental instability, and partner cruelty to mother but also mother and child diet have shown to be associated with the EOP trajectory [12,13], as well as adolescence correlates such as peer problems, emotional difficulties, and high risk of affiliating with deviant peers [14,15]. Early risk factors also account for AO individuals, particularly parental instability [16], low IQ and under controlled temperament [17]. Concomitant risk factors in adolescents with conduct problems include high-risk sexual behaviour, high levels of academic difficulties, and substance use [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A literatura aponta associação de atitudes anti-sociais em adolescentes com déficit intelectual 8 , uso de medicamentos 8 , álcool 9 , drogas 9 , dificuldades na relação parental 8,9,10,11 , abuso infantil 11 , baixo nível sócio-econômico 8 , família numerosa, poucos amigos e baixo rendimento escolar 12 .…”
Section: Introductionunclassified